Ecological Niche Shifts Affect the Potential Invasive Risk of Rapistrum rugosum (L.) All. in China - Xian, Xiaoqing; Zhao, Haoxiang; Wang, Rui; Qiao, Huijie; Guo, Jianyang; Zhang, Guifen; Liu, Wanxue; Wan, Fanghao (Frontiers in Plant Science, 2022)
Ecological niche is a key concept that links species distributions. Ecological niche shifts are expected to affect the potential invasive risk of alien species. Rapistrum rugosum is an invasive agricultural weed in many countries. Wild populations of R. rugosum have been recorded in China, representing a great threat to the regional crops. Based on distribution records from different regions, the present study used an optimized MaxEnt model with “kuenm” to predict the potential distribution and estimate the invasive risk of R. rugosum in China. Ecological niche shifts strongly affected the potential invasive risk of R. rugosum in China. The two most important variables were annual temperature range (Bio7) and mean temperature of the coldest quarter (Bio11). The total suitable habitat for the species covered an area of 287.53 × 104 km2 and was mainly distributed in Southwest, Southeast, and Central China. Australia, Canada, Brazil, the United States, and Argentina accounted for over 90% of the inspection records of R. rugosum from Chinese entry ports during 2015–2018. The intercepted R. rugosum was frequently mixed in Glycine max, Hordeum vulgare, linseed, Triticum aestivum, and Sorghum bicolor. Moreover, 80% interceptions were recorded from the Tianjin, Guangdong, Nanjing, and Chengdu customs. Climatic conditions do not limit the establishment capability of R. rugosum in China. Our results provide a theoretical reference for the development of monitoring and control measures for this invasive weed.